Conservation on traditional Malay house from maintenance aspect / Mohd Hafizie Mohd Ros - Mohd Ros, Mohd Hafizie (Faculty of Architecture, Planning and Surveying, 2009)
From the early chapters of chapter 1 to chapter 6 ,1 have touched on the conservation and maintenance of a building. Maintenance is very important for particular building houses as traditional Malay houses in many regions around Bagan Datoh, Perak. Conservation also means preserving a heritage or historic remains of a country. All data and information on conservation and maintenance I have refine in chapter 1 and chapter 2. Whereas in chapter 4 1 will touch on many sites about the background research I was about traditional Malay house. Many talked about the issues now houses a traditional Malay houses, especially houses that day when his condition worsened. Many steps have been taken by the government to solve this problem. Just look at the state of Malacca and Penang. The houses there have long started to be treated with care by the government because they realize that these old houses have a high value estatik. Back to my study, in chapter 5 of chapter 'Findings and Analysis', I found that most defects that occur in old houses are destroyed. Decay often occurs because the presence of high water in the wood long period of time. So we should have started moving in the strict safeguard of heritage treasures.